Glucocorticoids and 11β-HSD1 are major regulators of intramyocellular protein metabolism. Issue 3 (June 2016) - Morgan, Stuart A; Hassan-Smith, Zaki K; Doig, Craig L; Sherlock, Mark; Stewart, Paul M; Lavery, Gareth G
Abstract : The adverse metabolic effects of prescribed and endogenous glucocorticoid excess, 'Cushing's syndrome', create a significant health burden. While skeletal muscle atrophy and resultant myopathy is a clinical feature, the molecular mechanisms underpinning these changes are not fully defined. We have characterized the impact of glucocorticoids upon key metabolic pathways and processes regulating muscle size and mass including: protein synthesis, protein degradation, and myoblast proliferation in both murine C2C12 and human primary myotube cultures. Furthermore, we have investigated the role of pre-receptor modulation of glucocorticoid availability by 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) in these processes. Corticosterone (CORT) decreased myotube area, decreased protein synthesis, and increased protein degradation in murine myotubes. This was supported by decreased mRNA expression of insulin-like growth factor (IGF1), decreased activating phosphorylation of mammalian target of rapamycin (mTOR), decreased phosphorylation of 4E binding protein 1 (4E-BP1), and increased mRNA expression of key atrophy markers including: atrogin-1, forkhead box O3a (FOXO3a), myostatin ( MSTN ), and muscle-ring finger protein-1 (MuRF1). These findings were endorsed in human primary myotubes, where cortisol also decreased protein synthesis and increased protein degradation. The effects of 11-dehydrocorticosterone (11DHC) (in murine myotubes) and cortisone (in human myotubes) on protein metabolism were indistinguishable from that of CORT/cortisol treatments. Selective 11β-HSD1 inhibition blocked the decrease in protein synthesis, increase in protein degradation, and reduction in myotube area induced by 11DHC/cortisone. Furthermore, CORT/cortisol, but not 11DHC/cortisone, decreased murine and human myoblast proliferative capacity. Glucocorticoids are potent regulators of skeletal muscle protein homeostasis and myoblast proliferation. Our data underscores the potential use of selective 11β-HSD1 inhibitors to ameliorate muscle-wasting effects associated with glucocorticoid excess.